The Role and Function of The Financial Services Authority in The Supervision and Protection of Consumers against Illegal Online Loans - Yenny Ratnasari; Febby Mustikasari; Ichsandi Naufal Putra Perdana; Alvyan Miftahul Huda; Narendra Khairafi Cahyandi; Tania Shapna Putri (Proceeding International Conference Restructuring and Transforming Law, 2023)
This journal with the title "The Role and Functions of the Financial Services Authority in Consumer Supervision and Protection of Illegal Online Loans" was prepared using a normative juridical approach with data collection techniques with the help of various materials available in the library. This journal aims to convey information related to the functions, powers and duties of the Financial Services Authority according to Law no. 21 of 2011, online lending practices in Indonesia, and the supervision of the Financial Services Authority against consumers of illegal online loans in Indonesia. In addition, the purpose of compiling this journal is as educational material for the public if they are going to make online loans, they should be done in a legal way through the Financial Services Authority. If you make an online loan illegally, it will cause material losses for the borrower himself and will not get any protection from the Financial Services Authority.